The Transcultural Critic: Sabahattin Ali and Beyond - Ozil, Seyda; Hofmann, Michael; Laut, Jens-Peter; Dayioglu-Yücel, Yasemin; Zierau, Cornelia (Universitätsverlag Göttingen, 2017)
The central theme of this volume is the work of Sabahattin Ali, the Turkish author and translator from German into Turkish who achieved posthumous success with his novel Kürk Mantolu Madonna (The Madonna in the Fur Coat). Our contributors analyze this novel, which takes place largely in Germany, and several other texts by Ali in the context of world literature, (cultural) translation, and intertextuality. Their articles go far beyond the intercultural love affair that has typically dominated the discussion of Madonna. Other articles consider Zafer Şenocak's essay collection Deutschsein and transcultural learning through picture books. An interview with Selim Özdoğan rounds out the issue.